Mengukur Wayang Ukur Karya Ki Sukasman - -, Sukirno (Institut Seni Indoensia Surakarta, 2010)
wayang Purwa, is one kind of puppet that has distinctive characteristics with humans in it a reflection of disposition. Typology thus, hard to find from a variety of ethnic art that is in the archipelago. Distinctive shape with a depiction of what is known than what is seen, is a distinctive characteristic of said visually unique way. In the development of new wayang come with a variety of concepts and styles pakelirannya, not to mention also the doll child. Since the days of Demak until now always appear wanda wanda new in order perfected. One is the